2000
DOI: 10.1243/0954409001531270
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intermittent lubrication on the fatigue life of pearlitic rail steel in rolling-sliding contact

Abstract: Railway¯ange lubrication can be unreliable, resulting in intermittent rather than continuous lubrication. Twin-disc contact simulation tests were carried out to investigate the in¯uence of intermittent lubrication on rail steel fatigue life, using both a colloidal suspension of molybdenum disulphide in an oil carrier¯uid (similar to a commercial¯ange lubrication product) and water. A brief interruption of the lubricant supply during molybdenum disulphide lubrication produced rapid surface failure of the rail s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…For the left crack tip (Figure 4a), K I shows a rise with increasing crack size, but is small even for a 15mm crack. For comparison a threshold stress intensity factor of 6 MPa.m 1/2 for tensile growth of cracks in carbon steel is available from Otsuka et al [15] and has been applied in previous work on crack growth in rail steel [16,17]. The mode II data for the left crack tip (Figure 4b) shows much larger stress intensity factor values, but a low sensitivity to crack size of the total range during passage of the contact.…”
Section: Resultsmentioning
confidence: 99%
“…For the left crack tip (Figure 4a), K I shows a rise with increasing crack size, but is small even for a 15mm crack. For comparison a threshold stress intensity factor of 6 MPa.m 1/2 for tensile growth of cracks in carbon steel is available from Otsuka et al [15] and has been applied in previous work on crack growth in rail steel [16,17]. The mode II data for the left crack tip (Figure 4b) shows much larger stress intensity factor values, but a low sensitivity to crack size of the total range during passage of the contact.…”
Section: Resultsmentioning
confidence: 99%
“…This was not conducted for a railway application, but it did reveal the crucial involvement of fluids in the generation of cracks for this contact configuration. The effects of changes between lubricated and unlubricated contact were also investigated, and this has continued to receive attention since it is an inevitable aspect of rail operation (Tyfour et al, 1996;Fletcher and Beynon, 2000a). Way suggested that the lubricant acted as a hydraulic pressure transmitter in the manner of mechanism 2 in Fig.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…The latter can occur due to leaking trains or lubricant deliberately applied at the wheel flange/rail gauge contact in sharp curves to prevent excessive wear, noise and rail corrugation. [1][2][3] The oil lubricant is supplied between the wheel and rail generally using mobile lubricators, wayside lubricators or on-board lubricators. High-viscosity liquids can form a film between the wheel and rail and this can reduce the levels of traction.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, contamination by oil can affect crack growth due to rolling contact fatigue in a similar manner as to water; if the lubricant is left on the rail then there may be sufficient time for the oil to seep into a crack before it is rolled over by the wheel. 2 The metro in Mexico City is extensively used: last year more than 1,600,000,000 journeys were made on this system. It has 226.48 km of track spread over 12 lines.…”
Section: Introductionmentioning
confidence: 99%